Pengaruh Locus of Control, Perencanaan dean Literasi Keuangan terhadap Perilaku Keuangan UMKM - Salma Juliana Fadilah; Eko Purwanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
MSMEs are one of the drivers of the economy in Indonesia, in carrying out their business activities MSMEs are definitely influenced by the environment with the existence of self-control, financial planning and financial knowledge in those who carry out activities so that the business they run develops and creates good financial behavior. Behavioral finance is an attitude in which a person is able to consider and plan how to obtain a budget to meet business and individual needs. This study aims to analyze the effect of locus of control, financial planning, and financial literacy on financial behavior. The population in this study is MSMEs in Magetan Regency which are engaged in food and beverages. The sampling technique was done by purposive sampling. The sampling technique used the Slovin formula. The sample used in this study were 186 respondents. The data used in this study are primary data and secondary data, namely data from questionnaires from the answers of 186 respondents. The analysis technique in this study uses Partial Least Square (PLS). The results showed that locus of control, financial planning, and financial literacy had a significant positive effect on financial behavior. Keywords: Locus of Control; Financial Planing; Financial Literacy; Financial Behavior